T lymphocyte cell: A pivotal player in lung cancer - Wu, Yanan; Yuan, Meng; Wang, Chenlin; Chen, Yanfei; Zhang, Yan; Zhang, Jiandong (Frontiers in Immunology, 2023)
Lung cancer is responsible for the leading cause of cancer-related death worldwide which lacks effective therapies. In recent years, evidences on the understanding of the antitumor activity of the immune system have demonstrated that immunotherapy as one of the powerful alternatives in lung cancer therapy. T cells are the core of cellular immunotherapy which are critical for tumorigenesis and treatment of lung cancer. Based on the different expression of surface molecules and functional points, T cells can be subdivided into regulatory T (Treg) cells, T helper cells, cytotoxic T lymphocytes (CTL) and other unconventional T cells, including γδ T cells, nature killer T (NKT) cells and mucosal-associated invariant T (MAIT) cells. Advances in our understanding of T cells functional mechanism will lead to a number of clinical trials on the discovery and development of new treatment strategies. Thus, we summarize the biological functions and regulations of T cells on tumorigenesis, progression, metastasis and prognosis in lung cancer. Furthermore, we discuss the current advancements of technologies and potentials of T cells oriented therapeutic targets for lung cancer.